Law's Memories - Howard, Matt. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book discusses the relationship between law and memory and explores the ways in which memory can be thought of as contributing to legal socialization and legal meaning-making. Against a backdrop of critical legal pluralism which examines the distributedness of law(s), this book introduces the notion of mnemonic legality. It emphasises memory as a resource of law rather than an object of law, on the basis of how it substantiates senses of belonging and comes to frame inclusions and exclusions from a national community on the basis of linear-trajectory and growth narratives of nationhood. Overall, it explores the sensorial and affective foundations of law, implicating memory and perceptions of belonging within this process of creating legality and legitimacy. By identifying how memory comes to shape and inform notions of law, it contributes to legal consciousness research and to important questions informing much socio-legal research. Matt Howard is Lecturer in Law at the University of Kent, UK. .
Chapter 1: Introduction -- Chapter 2: Law and memory -- Chapter 3: Memory, time, and law -- Chapter 4: Being and meaning: the performance of historical truth -- Chapter 5: Elasticity of co-ordinated belonging -- Chapter 6: Conclusion.
Keywords: Law and the social sciences; Collective memory; Law -- Philosophy; Law -- History; Identity politics; Political sociology; Culture; Socio-Legal Studies; Memory Studies; Theories of Law, Philosophy of Law, Legal History; Identity Politics; Political Sociology; Sociology of Culture